A Class in Translation Service Provision for Students of Applied Linguistics UMCS - Klimkowski, Konrad; Klimkowska, Katarzyna (2024)
This study presents how students of translation at the Department of Applied Linguistics UMCS assessed the class dedicated to translation service provision competence. Analysed are data in the pre-test and post-test questionnaires taken by 30 (pre-test) and 21 (post-test) class participants in its initial implementation in the academic year 2022/23. Results indicate a general sense of satisfaction with class content and participation, and the open questions provide valuable information on potential areas of class enhancement. The article provides a general outline of the subject: content and methods. Apart from regular content-oriented classes, four workshops with language service provision professionals were held. Students had optional tasks to take: study tasks to explore selected aspects of business functioning in Poland and social media activities to build the brand associated with the class.
Keywords: translation service provision competence; translator education; portfolio management; solopreneurship; freelancing